2020
DOI: 10.1145/3369937
|View full text |Cite
|
Sign up to set email alerts
|

Search versus Decision for Election Manipulation Problems

Abstract: Most theoretical definitions about the complexity of manipulating elections focus on the decision problem of recognizing which instances can be successfully manipulated, rather than the search problem of finding the successful manipulative actions. Since the latter is a far more natural goal for manipulators, that definitional focus may be misguided if these two complexities can differ. Our main result is that they probably do differ: If integer factoring is hard, then for election manipulation, election bribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…Myself, I have found self-reducibility and its generalizations to be useful in understanding topics ranging from election manipulation [HHM13] to backbones of and backdoors to Boolean formulas [HN17,HN19] to the complexity of sparse sets [HS95], space-efficient language recognition [HOT94], logspace computation [HJ97], and approximation [HZ96,HH03].…”
Section: Discussionmentioning
confidence: 99%
“…Myself, I have found self-reducibility and its generalizations to be useful in understanding topics ranging from election manipulation [HHM13] to backbones of and backdoors to Boolean formulas [HN17,HN19] to the complexity of sparse sets [HS95], space-efficient language recognition [HOT94], logspace computation [HJ97], and approximation [HZ96,HH03].…”
Section: Discussionmentioning
confidence: 99%
“…6. In the related setting of voting, there are in fact cases where the complexity of search problems and their corresponding decision problems differs (Hemaspaandra, Hemaspaandra, & Menton, 2020).…”
Section: Search Problems As Pointed Out Bymentioning
confidence: 99%
“…Further, there are two variants of control by partition of candidates, one with runoff (where both subgroups send their winners to the final round) and one without (where the winners of one subgroup face all candidates of the other in the final round). Hemaspaandra, Hemaspaandra, and Menton [35] showed that certain destructive variants of these problems in fact are the same. In this paper, we will not consider any cases of control by partition, though.…”
Section: Introductionmentioning
confidence: 97%